The Effectiveness of Islamic Integrative Cognitive Restructuring Group Counseling Techniques in Improving Students’ Academic Resilience - Willya Zahara; Masril Masril; Rafsel Tas'adi; Silvianetri Silvianetri; Dasril Dasril (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2026)
This research is motivated by the low academic resilience of students at MAN 3 Padang Panjang, characterized by low self-confidence in facing academic difficulties, weak self-control, high academic anxiety, and low persistence in completing assignments. This study aims to test the effectiveness of group counseling with Islamic integrative cognitive restructuring techniques in improving students’ academic resilience. The study used a quasi-experimental method with a pretest–posttest control group design. The research sample consisted of 30 students selected through a purposive sampling technique and divided by random assignment into experimental and control groups. Data were collected using an academic resilience scale whose validity and reliability have been tested. Data analysis was carried out using the Independent Samples t-test and N-gain analysis. The results showed a significant difference between the experimental and control groups (t = 6.916; p < 0.05). The N-gain value of 0.22 indicates an increase in the low category, but remains practically meaningful. The increase occurred in the aspects of confidence, control, composure, and commitment. On the other hand, the control group showed a trend toward decreased academic resilience scores. This finding indicates that the intervention not only contributes to increased resilience but also has the potential to act as a psychological buffer against the declining tendency of students’ academic resilience. These findings suggest that group counseling using Islamic integrative cognitive restructuring techniques can be an alternative guidance and counseling service for improving students’ academic resilience, particularly in Islamic educational settings.